Neutrophil-like cells derived from the HL-60 cell-line as a genetically-tractable model for neutrophil degranulation. - Suhani B Bhakta; Stefan M Lundgren; Bethany N Sesti; Barbara A Flores; Emel Akdogan; Sean R Collins; Frances Mercer (PLoS ONE, 2024)
Research on neutrophil biology has been limited by the short life span and limited genetic manipulability of these cells, driving the need for representative and efficient model cell lines. The promyelocytic cell line HL-60 and its subline PLB-985 can be differentiated into neutrophil-like cells (NLCs) and have been used to study neutrophil functions including chemotaxis, phagocytosis, endocytosis, and degranulation. Compared to neutrophils derived from hematopoietic stem cells, NLCs serve as a cost-effective neutrophil model. NLCs derived from both HL-60 and PLB-985 cells have been shown to perform degranulation, an important neutrophil function. However, no study has directly compared the two lines as models for degranulation including their release of different types of mobilizable organelles. Furthermore, Nutridoma, a commercially available supplement, has recently been shown to improve the chemotaxis, phagocytosis, and oxidative burst abilities of NLCs derived from promyelocytic cells, however it is unknown whether this reagent also improves the degranulation ability of NLCs. Here, we show that NLCs derived from both HL-60 and PLB-985 cells are capable of degranulating, with each showing markers for the release of multiple types of secretory organelles, including primary granules. We also show that differentiating HL-60 cells using Nutridoma does not enhance their degranulation activity over NLCs differentiated using Dimethyl Sulfoxide (DMSO) plus Granulocyte-colony stimulating factor (G-CSF). Finally, we show that promyelocytic cells can be genetically engineered and differentiated using these methods, to yield NLCs with a defect in degranulation. Our results indicate that both cell lines serve as effective models for investigating the mechanisms of neutrophil degranulation, which can advance our understanding of the roles of neutrophils in inflammation and immunity.